2018
DOI: 10.1021/acs.est.7b06500
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Bioavailability, Speciation, and Phytotoxicity of Tungsten (W) in Soil Affect Growth and Molybdoenzyme Activity of Nodulated Soybeans

Abstract: Increasing use of tungsten (W)-based products opened new pathways for W into environmental systems. Due to its chemical alikeness with molybdenum (Mo), W is expected to behave similarly to its “twin element”, Mo; however, our knowledge of the behavior of W in the plant–soil environment remains inadequate. The aim of this study was to investigate plant growth as well as W and nutrient uptake depending on soil chemical properties such as soil pH and texture. Soybean (Glycine max cv. Primus) was grown on two acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 58 publications
8
21
1
Order By: Relevance
“…The results are in agreement with previous findings for another species, Triticum aestivum, which reported that biomass was not influenced by low tungsten concentrations in soil [34,35]. A reduction in biomass production was discovered in soils only with very high tungsten concentrations of up to 5000 mg kg −1 for Glycine max [30] and 2600 mg kg −1 for Helianthus annuus [26]. Under the experimental conditions adopted, tungsten did not show any visual toxicity effects on plants.…”
Section: Biomass Productionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results are in agreement with previous findings for another species, Triticum aestivum, which reported that biomass was not influenced by low tungsten concentrations in soil [34,35]. A reduction in biomass production was discovered in soils only with very high tungsten concentrations of up to 5000 mg kg −1 for Glycine max [30] and 2600 mg kg −1 for Helianthus annuus [26]. Under the experimental conditions adopted, tungsten did not show any visual toxicity effects on plants.…”
Section: Biomass Productionsupporting
confidence: 92%
“…During this period, the spiked soils were maintained in loosely covered polypropylene containers. To obtain the greatest homogeneity, once a week soils were gently mixed by a shovel, and watered with deionized water once a month as necessary [30].…”
Section: Soilsmentioning
confidence: 99%
See 3 more Smart Citations